Opportunities for improving opioid disposal practices in the Veterans Health Administration. (14th April 2021) - Giannitrapani, Karleen F; Brown-Johnson, Cati; McCaa, Matthew; Mckelvey, Jeremiah; Glassman, Peter; Holliday, Jesse; Sandbrink, Friedhelm; Lorenz, Karl A
Abstract: Purpose: The potentially vast supply of unused opioids in Americans' homes has long been a public health concern. We conducted a needs assessment of how Veterans Affairs (VA) facilities address and manage disposal of unused opioid medications to identify opportunities for improvement. Methods: We used rapid qualitative content analysis methods with team consensus to synthesize findings. Data were collected in 2 waves: (1) semistructured interviews with 19 providers in October 2019 and (2) structured questions to 21 providers in March to April of 2020 addressing how coronavirus disease 2019 (COVID-19) changed disposal priorities. Results: While many diverse strategies have been tried in the VA, we found limited standardization of advice on opioid disposal and practices nationally. Providers offered the following recommendations: target specific patient scenarios for enhanced disposal efforts, emphasize mail-back envelopes, keep recommendations to providers and patients consistent and reinforce existing guidance, explore virtual modalities to monitor disposal activity, prioritize access to viable disposal strategies, and transition from pull to push communication. These themes were identified in the fall of 2019 and remained salient in the context of the COVID-19 pandemic. Conclusion: A centralized VA national approach could include proactive communication with patients and providers, interventions tailored to specific settings and populations, and facilitated access to disposal options. All of the above strategies are feasible in the context of an extended period of social distancing.